Anschlussbahnen: Erschließung von Schienengüterverkehrspotenzialen. - Liedtke, Gernot; Martin, Ullrich; Ott, Anselm (Deutscher Verkehrs-Verl., 2007)
Der heutige wissenschaftliche Stand in der Güterverkehrsprognostik und Güterverkehrsplanung besteht aus der Kombination von verschiedenen Modellelementen aus dem klassischen 4-Stufen-Algorithmus der Verkehrsplanung (Verkehrserzeugung, Verkehrsverteilung, Verkehrsaufteilung, Verkehrsumlegung). Dabei wird Verkehrsentstehung und -verteilung in der Regel mit aggregierten Modellelementen erklärt (wie zum Beispiel regionale Produktionsfunktionen). Gibt es bessere Ansätze? difu

During the project CORRECT of DEUFRAKO corridors with high volume of transport could be identified for rail freight transport with single wagons in Germany. This gave the chance to determine the distribution of the transport volume of freight branch lines relating to the geographic area of Germany and to identify corridors with highest volume of transport. For the determination of the distribution of the transport volume a freight branch line data base was used and a model for the calculation of the volume of transport relating to defined geographic area was developed. Both were linked with a geographic information system (GIS). This made it possible to achieve a scientific contribution for a realistic line oriented modelling of volume of transport in rail freight transport. difu
Keywords: Verkehr; Verkehrsaufkommen; Güterverkehr; Schienengüterverkehr; Verkehrsplanung; Verkehrsmodell; Verkehrsnachfrage; Verkehrsprognose; Verkehrsforschung; Anschlussbahn; Verkehrsträger; Geographisches Informationssystem